Age of Alcohol Initiation Matters: Examining Gender Differences in the Recency and Frequency of Alcohol Use Across Adolescence Using a Sample of Impoverished Minority Adolescents. Issue 1 (January 2019) - Tomek, Sara; Bolland, Kathleen A.; Bolland, John M.; Hooper, Lisa M.; Church, Wesley T.; Bolland, Anneliese C.
While previous research has shown alcohol use to increase developmentally throughout adolescence, the age of alcohol initiation has rarely been incorporated into developmental trajectories. Simultaneous estimation of the effects of early alcohol initiation was made in relation to the recency and frequency of alcohol use utilizing a sample of 1, 209 low-income, minority adolescents initiating alcohol between 12 and 18. Significant effects of both age of alcohol initiation and gender were found. Initial alcohol use was higher the later the adolescent initiated alcohol use. Following initiation, trajectories of the recency and frequency of alcohol use for female adolescents increased more rapidly the earlier they initiate alcohol use, while trajectories for male adolescents increased independent of their year of initiation. Modeling age of initiation using piecewise growth models provided more informative results regarding early alcohol initiation effects as compared to traditional longitudinal model.